Simulation of sheath voltage, losses and loss factor of high voltage underground cable using MATLAB/Simulink - Mahmood Natiq Abed; Osamah Abdulsalam Suhry; Mohammed Ahmed Ibrahim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
In this paper, 22 equations for high voltage cable sheaths are simulated in one model. The model outputs are represented by cable sheath voltages, circulating currents, losses and factors, eddy currents, losses, and factors in both tides laying states (trefoil and flat) when grounding the sheaths from a single point, two points, or cross-link. These values depend on the cable manufacturing's specific factors. The other factors affecting these values are specific to the laying and operation: the load current, the length of the cable to be laid out, the spacing between the cables, and the power frequency. This research aims to reduce or eliminate the losses of the cable sheath. These two types of currents cause losses that may sometimes equal the losses of the conductor of the cable carrying the load current. Which reduces the capacity of the cable and reduces the heat dissipation of the cable into the soil and damages it. Electricians are at risk of electrocution due to the high voltages of the sheaths when there is no current in the sheaths. Therefore, these currents and voltages must be eliminated by making a new model that studies the effect of all these factors on them.